Education, lifetime labor supply, and longevity improvements - Miguel Sanchez-Romero; Hippolyte d'Albis; Alexia Fürnkranz-Prskawetz (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2016)
This paper presents an analysis of the differential role of mortality for the optimal schooling and retirement age when the accumulation of human capital follows the so-called "Ben-Porath mechanism". We set up a life-cycle model of consumption and labor supply at the extensive margin that allows for endogenous human capital formation. This paper makes two important contributions. First, we provide the conditions under which a decrease in mortality leads to a longer education period and an earlier retirement age. Second, those conditions are decomposed into a Ben-Porath mechanism and a lifetime-human wealth effect vs. the years-to-consume effect. Finally, using US and Swedish data for cohorts born between 1890 and 2000, we show that our model can match the empirical evidence.
Keywords: I25; J10; J24; J26; 330; Sterblichkeit; Schulbesuch; Altersgrenze; Humankapital; Lebenszyklushypothese; Haushaltsstatistik; Arbeitsangebot; Vermögen; Kohortenanalyse; Empirische Methode; USA; Schweden